Environmentally Sustainable Alkyd-Based SiO₂–CuO Nanocoatings for Industrial Corrosion Protection: Synergistic, Structural, and Electrochemical Evaluation - Khazaal, Khazaal Hameed; Alwash, Omar A.; Karafe, Abbas Mezaal (Annales de chimie (Paris. 1914), 2025)
This study investigates the development of anticorrosion alkyd coatings enhanced with a hybrid nanofiller system comprising silicon dioxide (SiO₂) and copper oxide (CuO) nanoparticles. The primary objective was to determine the optimal nanoparticle ratio and loading concentration to improve the protective performance on mild steel substrates. Electrochemical impedance spectroscopy (EIS) revealed that a SiO₂:CuO weight ratio of 0.61:0.39 at a total concentration of 0.84 wt.% exhibited the highest corrosion resistance, achieving an impedance of 8.79 × 10⁶ Ω·cm². Scanning electron microscopy (SEM) confirmed a uniform nanofiller distribution with no microstructural defects. Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analyses verified the successful chemical incorporation and crystallinity of the nanocomposite. Thermogravimetric analysis (TGA) indicated enhanced thermal stability, while adhesion testing following ASTM D3359 Method A demonstrated improved bonding with the substrate. Compared to a commercial epoxy-phenolic coating (TK™-34), the developed coating retained 69% of its initial impedance after 72 hours of salt spray exposure, indicating superior durability. The synergistic interaction between hydrophobic CuO and insulating SiO₂ significantly contributed to enhanced barrier and electrochemical properties. These findings highlight the practical viability of SiO₂–CuO nanocomposite coatings in extending the service life of steel infrastructures, offering a cost-effective and sustainable alternative to conventional protective systems.